Keterampilan Digital (AI) Bagi Pendidik Seni: Mengintegrasikan Seni dan Teknologi dalam Pembelajaran yang Kreatif - Chica Anggraeni; Hartono; Restu Lanjari (PT. Saha Kreasi Indonesia, 2025)
This study aims to reveal the urgency of developing artificial intelligence (AI)-based digital skills for art educators as a key requirement for the successful integration of art and technology in creative learning in the digital age. Through a systematic literature review of recent sources (2019–2025), the results show that generative AI has been proven to play a role as a collaborative partner that changes the paradigm of arts education to “post-human art education” (Pavlik & Pavlik, 2024; Mayo, 2024). AI is capable of objectively analyzing students' work (visual patterns, musical composition, dance movements), providing instant feedback, creating interactive simulations, and personalizing learning through the 5E model (Engage-Explore-Explain-Elaborate -Evaluate) model, thereby significantly improving students' understanding of the concepts of form, space, tone, movement, and composition while strengthening their creativity, critical thinking, and visual-spatial problem-solving skills. However, the success of this transformation depends entirely on the digital competence of art educators in AI. Without mastery of AI, educators will only become passive consumers of technology, and students risk losing their competitiveness in the global creative industry. Therefore, this study recommends three concrete steps: (1) integrating the compulsory course “Artificial Intelligence for Art Education” into the art teacher education curriculum, (2) implementing national AI skills certification for art educators, and (3) developing a locally-based AI platform for inclusive art learning. Thus, art educators will not only be able to survive technological disruption, but also become pioneers in the birth of a generation of Indonesian digital artists-creators who are competitive at the global level.